Cryptogenic recurrent spontaneous intracranial epidural hematoma: A case report and literature review - Xu, Min; Xue, Ya; Chao, Xiaofeng; Chen, Zhenglou; Wang, Yunjiang; Huo, Xuqi; Ji, Xiang; Wang, Hongshen (Frontiers in Neurology, 2023)
Background Spontaneous epidural hematoma (EDH) has been suggested to be associated with adjacent infective pathologies, dural vascular malformations, extradural metastases, or coagulopathies. Cryptogenic spontaneous EDH is extremely rare. Case presentation The present study reports the case of a cryptogenic spontaneous EDH in a young woman following sexual intercourse. She was diagnosed with consecutive EDH at three different sites within a short time. After three timely operations, a satisfactory outcome was achieved. Conclusion EDH should be investigated when a young patient develops headaches and shows signs of increased ICP after emotional hyperactivity or hyperventilation. If early diagnosis and surgical decompression can be carried out in time, the prognosis would be satisfactory.